Locust bean gum and sodium alginate based interpenetrating polymeric network microbeads encapsulating Capecitabine: Improved pharmacokinetics, cytotoxicity &in vivo antitumor activity - Upadhyay M.; Adena S.K.R.; Vardhan H.; Yadav S.K.; Mishra B. (My University, 2025)
A combination of biopolymers sodium alginate and locust bean gum has been used to prepare an interpenetrating polymeric network of an anticancer drug Capecitabine by ionotropic gelation method. For the optimization 32 levels, a full factorial design was employed to examine the influence of independent factors, i.e. polymer ratio and cross-linker concentration on responses particle size and drug entrapment. The obtained optimized formulation was examined for solid-state characterization, swelling study, in vitro drug release, SRB study, oral toxicity study, in vivo pharmacokinetic and in vivo antitumor study. The results of all the studies performed were found suitable in extending the release of a short elimination half-life drug with improved bioavailability and suggesting it to be safe and effective for oral drug delivery in treating colon cancer. © 2019 Elsevier B.V.